踝关节康复六杆机构的性能分析 - 尹姣姣; 梅瑛; 李瑞琴; 秦伟桦 (Jixie chuandong)
A six-bar mechanism which can help patients achieve ankle rehabilitation is presented.The mechanism vector equation is established firstly.The locus equations of its output points are obtained.Through simulating the kinematic characteristics of the aided process,the output point ankle and tiptoe displacement,velocity,acceleration diagrams are obtained,then the suitable speed of the movement of the crank mechanism is analyzed.The simulation results of the analysis provided a theoretical basis to human action point selection,the ways to develop ankle rehabilitation training and the corresponding control mode.